POLICY IMPLEMENTATION FOR HIV/AIDS AND SEXUALLY TRANSMITTED INFECTIOUS DISEASE PROGRAMS IN THE FIRST LEVEL OF HEALTH FACILITY - Suparmi Suparmi; Triana Sri Hardjanti; Hesti Kurniasih (Jurnal Riset Kesehatan, 2020)
The number of HIV/AIDS and Sexually Transmited Infectious Diseases (PIMS) incidence in Indonesia, especially in Central Java are growing every year. Provincial government set a regulation in controlling disease that refers to the HIV/ AIDS Control Program and PIMS in the First Level of Health Facilities by the Ministry of Health in 2016. It is hoped that this program can break the chain of HIV/AIDS and PIMS cases while at the same time making a generation that healthy and productive quality. The aim of this study was to determine the implementation of programs to control HIV/AIDS and PIMS in Banyumas regency. The design of this study was descriptive qualitative through in-depth interviews. The main informants were ten HIV Counseling and Testing (KTHIV) of Public Health Center, triangulation informants were People Living With HIV/AIDS (PLWHA) patients, Clinical Doctors, Head of Department of Health Services P2P. The data were collected by in-depth interview technique. In addition to the interview, a survey was also conducted with PLWHA. Processing and analysis of data were using taxonomic analysis. The implementation of HIV/AIDS control program policies has not been optimal in its implementation. The lack of optimal implementation of HIV/AIDS and PIMS prevention policies is due to several aspects, i.e. policy accuracy, implementation accuracy, target accuracy, environmental accuracy, and process accuracy. Increasing monitoring and evaluation related to a program's policies is needed. Morover,  it is important to improve the quality of human resources and careful planning related to the control program.